KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia) - GUGUS ALAM BAKTIOWIDHI ; Dr. Djumahir, SE, MM (Manajemen FEB - UB, 2018)
This study aims to: 1) To know and analyze the financial performance in terms of economic value added (EVA) dan market value added (MVA) before and after mergers and acquisitions in manufacturing companies listed on the IDX 2010-2013 period 2) To know and analyzing the difference of financial performance in terms of economic value added (EVA) before and after mergers and acquisitions at manufacturing companies listed on IDX 3) To know and analyze the difference of financial performance reviewed from market value added (MVA) before and after mergers and acquisitions in manufacturing companies listed on the IDX. This research uses descriptive research type by describing variable to describe company's financial performance which is known through economic value added (EVA) dan market value added (MVA) analysis, with object used in research is manufacturing company merger and acquisition which listed in IDX number 4 company. The results showed that the financial performance before and after mergers and acquisitions in manufacturing companies studied can be known that there is a tendency to decrease when viewed from economic value added (EVA). The analysis results can be seen that the financial performance of market value added (MVA) shows an increase. Keywords: Financial Performance, Mergers and Acquisitions